Respuesta :
Hey there, hope I can help!
NOTE: Look at the image/images for useful tips
[tex]\left(h+c,\:k\right),\:\left(h-c,\:k\right)[/tex]
[tex]\frac{\left(x-h\right)^2}{a^2}-\frac{\left(y-k\right)^2}{b^2}=1\:\mathrm{\:is\:the\:standard\:equation\:for\:a\:right-left\:facing:H}[/tex]
with the center of (h, k), semi-axis a and semi-conjugate - axis b.
NOTE: H = hyperbola
[tex]9x^2-y^2-36x-4y+23=0 \ \textgreater \ \mathrm{Subtract\:}23\mathrm{\:from\:both\:sides}[/tex]
[tex]9x^2-36x-4y-y^2=-23[/tex]
[tex]\mathrm{Factor\:out\:coefficient\:of\:square\:terms}[/tex]
[tex]9\left(x^2-4x\right)-\left(y^2+4y\right)=-23[/tex]
[tex]\mathrm{Divide\:by\:coefficient\:of\:square\:terms:\:}9[/tex]
[tex]\left(x^2-4x\right)-\frac{1}{9}\left(y^2+4y\right)=-\frac{23}{9}[/tex]
[tex]\mathrm{Divide\:by\:coefficient\:of\:square\:terms:\:}1[/tex]
[tex]\frac{1}{1}\left(x^2-4x\right)-\frac{1}{9}\left(y^2+4y\right)=-\frac{23}{9}[/tex]
[tex]\mathrm{Convert}\:x\:\mathrm{to\:square\:form}[/tex]
[tex]\frac{1}{1}\left(x^2-4x+4\right)-\frac{1}{9}\left(y^2+4y\right)=-\frac{23}{9}+\frac{1}{1}\left(4\right)[/tex]
[tex]\mathrm{Convert\:to\:square\:form}[/tex]
[tex]\frac{1}{1}\left(x-2\right)^2-\frac{1}{9}\left(y^2+4y\right)=-\frac{23}{9}+\frac{1}{1}\left(4\right)[/tex]
[tex]\mathrm{Convert}\:y\:\mathrm{to\:square\:form}[/tex]
[tex]\frac{1}{1}\left(x-2\right)^2-\frac{1}{9}\left(y^2+4y+4\right)=-\frac{23}{9}+\frac{1}{1}\left(4\right)-\frac{1}{9}\left(4\right)[/tex]
[tex]\mathrm{Convert\:to\:square\:form}[/tex]
[tex]\frac{1}{1}\left(x-2\right)^2-\frac{1}{9}\left(y+2\right)^2=-\frac{23}{9}+\frac{1}{1}\left(4\right)-\frac{1}{9}\left(4\right)[/tex]
[tex]\mathrm{Refine\:}-\frac{23}{9}+\frac{1}{1}\left(4\right)-\frac{1}{9}\left(4\right) \ \textgreater \ \frac{1}{1}\left(x-2\right)^2-\frac{1}{9}\left(y+2\right)^2=1 \ \textgreater \ Refine[/tex]
[tex]\frac{\left(x-2\right)^2}{1}-\frac{\left(y+2\right)^2}{9}=1[/tex]
Now rewrite in hyperbola standardform
[tex]\frac{\left(x-2\right)^2}{1^2}-\frac{\left(y-\left(-2\right)\right)^2}{3^2}=1[/tex]
[tex]\mathrm{Therefore\:Hyperbola\:properties\:are:}\left(h,\:k\right)=\left(2,\:-2\right),\:a=1,\:b=3[/tex]
[tex]\left(2+c,\:-2\right),\:\left(2-c,\:-2\right)[/tex]
Now we must compute c
[tex]\sqrt{1^2+3^2} \ \textgreater \ \mathrm{Apply\:rule}\:1^a=1 \ \textgreater \ 1^2 = 1 \ \textgreater \ \sqrt{1+3^2}[/tex]
[tex]3^2 = 9 \ \textgreater \ \sqrt{1+9} \ \textgreater \ \sqrt{10}[/tex]
Therefore the hyperbola foci is at [tex]\left(2+\sqrt{10},\:-2\right),\:\left(2-\sqrt{10},\:-2\right)[/tex]
For the vertices we have [tex]\left(2+1,\:-2\right),\:\left(2-1,\:-2\right) [/tex]
Simply refine it
[tex]\left(3,\:-2\right),\:\left(1,\:-2\right)[/tex]
Therefore the listed coordinates above are our vertices
Hope this helps!
NOTE: Look at the image/images for useful tips
[tex]\left(h+c,\:k\right),\:\left(h-c,\:k\right)[/tex]
[tex]\frac{\left(x-h\right)^2}{a^2}-\frac{\left(y-k\right)^2}{b^2}=1\:\mathrm{\:is\:the\:standard\:equation\:for\:a\:right-left\:facing:H}[/tex]
with the center of (h, k), semi-axis a and semi-conjugate - axis b.
NOTE: H = hyperbola
[tex]9x^2-y^2-36x-4y+23=0 \ \textgreater \ \mathrm{Subtract\:}23\mathrm{\:from\:both\:sides}[/tex]
[tex]9x^2-36x-4y-y^2=-23[/tex]
[tex]\mathrm{Factor\:out\:coefficient\:of\:square\:terms}[/tex]
[tex]9\left(x^2-4x\right)-\left(y^2+4y\right)=-23[/tex]
[tex]\mathrm{Divide\:by\:coefficient\:of\:square\:terms:\:}9[/tex]
[tex]\left(x^2-4x\right)-\frac{1}{9}\left(y^2+4y\right)=-\frac{23}{9}[/tex]
[tex]\mathrm{Divide\:by\:coefficient\:of\:square\:terms:\:}1[/tex]
[tex]\frac{1}{1}\left(x^2-4x\right)-\frac{1}{9}\left(y^2+4y\right)=-\frac{23}{9}[/tex]
[tex]\mathrm{Convert}\:x\:\mathrm{to\:square\:form}[/tex]
[tex]\frac{1}{1}\left(x^2-4x+4\right)-\frac{1}{9}\left(y^2+4y\right)=-\frac{23}{9}+\frac{1}{1}\left(4\right)[/tex]
[tex]\mathrm{Convert\:to\:square\:form}[/tex]
[tex]\frac{1}{1}\left(x-2\right)^2-\frac{1}{9}\left(y^2+4y\right)=-\frac{23}{9}+\frac{1}{1}\left(4\right)[/tex]
[tex]\mathrm{Convert}\:y\:\mathrm{to\:square\:form}[/tex]
[tex]\frac{1}{1}\left(x-2\right)^2-\frac{1}{9}\left(y^2+4y+4\right)=-\frac{23}{9}+\frac{1}{1}\left(4\right)-\frac{1}{9}\left(4\right)[/tex]
[tex]\mathrm{Convert\:to\:square\:form}[/tex]
[tex]\frac{1}{1}\left(x-2\right)^2-\frac{1}{9}\left(y+2\right)^2=-\frac{23}{9}+\frac{1}{1}\left(4\right)-\frac{1}{9}\left(4\right)[/tex]
[tex]\mathrm{Refine\:}-\frac{23}{9}+\frac{1}{1}\left(4\right)-\frac{1}{9}\left(4\right) \ \textgreater \ \frac{1}{1}\left(x-2\right)^2-\frac{1}{9}\left(y+2\right)^2=1 \ \textgreater \ Refine[/tex]
[tex]\frac{\left(x-2\right)^2}{1}-\frac{\left(y+2\right)^2}{9}=1[/tex]
Now rewrite in hyperbola standardform
[tex]\frac{\left(x-2\right)^2}{1^2}-\frac{\left(y-\left(-2\right)\right)^2}{3^2}=1[/tex]
[tex]\mathrm{Therefore\:Hyperbola\:properties\:are:}\left(h,\:k\right)=\left(2,\:-2\right),\:a=1,\:b=3[/tex]
[tex]\left(2+c,\:-2\right),\:\left(2-c,\:-2\right)[/tex]
Now we must compute c
[tex]\sqrt{1^2+3^2} \ \textgreater \ \mathrm{Apply\:rule}\:1^a=1 \ \textgreater \ 1^2 = 1 \ \textgreater \ \sqrt{1+3^2}[/tex]
[tex]3^2 = 9 \ \textgreater \ \sqrt{1+9} \ \textgreater \ \sqrt{10}[/tex]
Therefore the hyperbola foci is at [tex]\left(2+\sqrt{10},\:-2\right),\:\left(2-\sqrt{10},\:-2\right)[/tex]
For the vertices we have [tex]\left(2+1,\:-2\right),\:\left(2-1,\:-2\right) [/tex]
Simply refine it
[tex]\left(3,\:-2\right),\:\left(1,\:-2\right)[/tex]
Therefore the listed coordinates above are our vertices
Hope this helps!
![Ver imagen DivineSolar](https://us-static.z-dn.net/files/d30/2c93f12c252a7065b81469ec84a2733b.png)
![Ver imagen DivineSolar](https://us-static.z-dn.net/files/d84/e958735e916ec4a4f7b84c949d557b60.png)